2007
DOI: 10.1016/j.brainres.2007.02.047
|View full text |Cite
|
Sign up to set email alerts
|

Axonal sprouting into the denervated spinal cord and synaptic and postsynaptic protein expression in the spinal cord after transplantation of bone marrow stromal cell in stroke rats

Abstract: We investigated whether compensatory reinnervation in the corticospinal tract (CST) and the corticorubral tract (CRT) is enhanced by administration of bone marrow stromal cells (BMSCs) after experimental stroke. Adult male Wistar rats were subjected to permanent right middle cerebral artery occlusion (MCAo). Phosphate-buffered saline (PBS, control, n=7) or 3 × 10 6 BMSCs in PBS (n=8) were injected into a tail vein at 1 day postischemia. The CST of the left sensorimotor cortices was labeled with DiI 2 days prio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 43 publications
4
55
1
Order By: Relevance
“…31 This limitation is due to a lack of neurotrophins, but also due to the presence of growth-IMs. 61 These growth-IMs include chondroitin sulfate proteoglycans (for example, neurocan, versican, phosphacan, and brevican), 22 Nogo-A, myelin-associated glycoprotein (MAG), and oligodendrocyte myelin glycoprotein (OMgp).…”
Section: Discussionmentioning
confidence: 99%
“…31 This limitation is due to a lack of neurotrophins, but also due to the presence of growth-IMs. 61 These growth-IMs include chondroitin sulfate proteoglycans (for example, neurocan, versican, phosphacan, and brevican), 22 Nogo-A, myelin-associated glycoprotein (MAG), and oligodendrocyte myelin glycoprotein (OMgp).…”
Section: Discussionmentioning
confidence: 99%
“…MCAO is a common model for induction of focal cerebral ischemia (Liu et al, 2007) and this method shows most reproducible and extensive lesions in spontaneously hypertensive rats (Traystman, 2003). Furthermore, the animals present a risk profile including hypertension and hypercholesterolemia which is frequently found in human stroke patients.…”
Section: Neural Markers After Mcao In the Rat Brainmentioning
confidence: 99%
“…As in stroke studies [23,[37][38][39], the delayed treatments of TBI promoted neurorestorative process in cortical tissue, such as axonal density and reorganization, which fosters improved behavioral function. Without reducing lesion volume, cell-based treatments of stroke in rat also improved functional recovery from the short term (4 weeks) to the long term (1 year) [41,42]. Therefore, the delayed low dose methamphetamine treatment of TBI in rats may improve functional outcome by enhancing biophysical functions of cerebral tissue in the recovery region, although the treatment did not reduce lesion volume and brain atrophy within 6 weeks post TBI.…”
Section: Discussionmentioning
confidence: 99%
“…Neuronal fiber reorganization after injury may play an important role in fuctional recovery [41,42]. We found that 12 hour post stroke methamphetamine treatment at an infusion dose of 1.0 mg/kg/hr for 24 hours in rats did not reduce infarct volume examined at 7 days post injury, but, did improve neurological scores in rats compared with saline treated controls [18].…”
Section: Discussionmentioning
confidence: 99%